The age of selfishness Ayn Rand, morality, and the financial crisis - Cunningham, Darryl 1960- (Abrams, 2015)
Using Rand's biography to illuminate the policies that led to the economic crash in the U.S. and in Europe and the global financial crisis of 2008, Cunningham shows how her philosophy continues to affect today's politics and policies, starting with her most noted disciple, economist Alan Greenspan (former chairman of the Federal Reserve). Cunningham also shows how right-wing conservatives, libertarians, and the Tea Party movement have co-opted Rand's teachings (and inherent contradictions) to promote personal gain and profit at the expense of the middle class